170k views
4 votes
I was wondering if someone can please help me I keep getting the wrong answer and I was just wondering if someone could explain it and help me

I was wondering if someone can please help me I keep getting the wrong answer and-example-1
User Smatyas
by
6.5k points

1 Answer

4 votes

Answer:


h(g(-5)) = 127

Step-by-step explanation:

Given


h(x) = 2x^2 - 1


g(x) = x - 3

Required

Find
h(g(-5))

First, we need to solve for
g(-5)


g(x) = x - 3

Substitute -5 for x


g(-5) = -5 - 3


g(-5) = -8

Substitute -8 for g(-5) in
h(g(-5))


h(g(-5)) =
h(-8)

Given that:


h(x) = 2x^2 - 1

Substitute -8 for x


h(-8) = 2(-8)^2 - 1


h(-8) = 2*64 - 1


h(-8) = 128 - 1


h(-8) = 127

Hence:


h(g(-5)) = 127

User Scott Bale
by
6.2k points